DOMESTIC VIOLENCE PERMITTED BY HUSBAND AGAINST WIFE FROM A CRIMINOLOGICAL PERSPECTIVE - Karina, Ica; Banjarnahor, Jupri Wandy (ANAYASA : Journal of Legal Studies, 2024)
From a perspective, this study aims to ascertain the causes of husbands' violence against wives and attempts to stop such violent acts. The data used to answer the problems in this research was obtained through a literature study by reading, quoting, studying, and reviewing existing literature or materials, as well as laws and regulations related to the problems studied. The research results show that the factors causing violence perpetrated by husbands against their wives are economic factors, partner behavioural factors, and psychological factors. Economic factors are the things that most often trigger domestic violence. This starts with the husband's duty, which should not only fulfil basic needs but also other needs that must be met. Environmental factors, namely the place and social environment, sometimes bring their own colour to a person's life. Psychology is one of the causes of domestic violence because the psychological condition of a wife is different and can also determine the size of the actions taken. Efforts made to overcome violence perpetrated by husbands against wives are preventive, curative, and medical. Preventive measures are social control measures carried out to prevent or reduce the possibility of undesirable things occurring in the future. Curative efforts are efforts to overcome domestic violence or actions taken to treat victims in an integrated manner. Medical efforts are efforts to overcome domestic violence by providing the services of a health worker again to undergo.